Quantification of Soil Water Retention Capacity in the Protected Water Management Area Žitný Ostrov (Slovakia) - Zdena Krnáčová; Mária Barančoková; Martin Labuda (Agriculture)
Water is a crucial resource in agriculture, but climate change has led to more frequent droughts, particularly at the start of the growing season, adversely affecting crop yields. This paper evaluates soil water retention capacity (SWRC) in the Protected Water Management Area Žitný ostrov, which is home to Slovakia’s most fertile soils and significant groundwater reserves. In our study, we adopted a new methodological approach and developed an algorithm for weighting selected physical parameters from the valued soil-ecological units (VSEUs) database, applicable to larger territorial units. To estimate SWRC, we used an algorithm based on the physical parameters of VSEUs, reclassifying them into 10 categories of cumulative water retention capacity (CWRC) and mapping SWRC in the model area. Most of the area demonstrates high water retention due to groundwater, but these sources are being increasingly depleted. Agriculture, as a significant contributor to groundwater pollution, must adapt to climate change by implementing crop management practices that reduce agrochemical seepage and preserve water supply. Regenerative agriculture and agroforestry, which enhance soil properties, are proposed as viable solutions. Additionally, infrastructure such as dams, ponds, and rainwater harvesting systems, along with the expansion of wetlands, can help capture and store water in areas with lower retention capacity. This study aims to identify critical zones with varying retention capacities and recommends crop rotation adjustments to prevent agrochemical seepage and enhance water retention. These practices are essential for sustaining agriculture while protecting water resources amidst global climate challenges.